The application of fast feedback in discovery learning on the achievement of critical thinking ability reviewed from adversity quotient - Narumi, Safira Aprillia; Kartono, Kartono (Department of Mathematics, Universitas Negeri Semarang, 2020)
The objectives of this research were (1) to discover the effectiveness of discovery learning model with fast feedback towards the students’ achievement of critical thinking abilities; and (2) to describe students' critical thinking abilities reviewed from adversity quotient. The research method and design used in this research was mix methods with sequential explanatory. The population of this research were 7th grade students of Junior High School 1 Semarang. Sampling for the experiment class and control class by means of cluster random sampling, and the selection of subjects using purposive sampling technique. The results showed that discovery learning with fast feedback was effective in achieving students' critical thinking abilities. The description of the subject's critical thinking abilities based on the adversity quotient showed that: (1) the climbers’ subjects could master four indicators of critical thinking, namely interpretation, analysis, inference, and evaluation; (2) the campers-climbers’ subjects could master two indicators of critical thinking, namely analysis and inference, and sufficiently master the indicators of interpretation and evaluation; and (3) the campers’ subjects has sufficiently master two indicators of critical thinking, namely infer